Gongs galore: phaleristic study of the relative risk of a healing art related New Year Honour. Issue 1158 (9th February 2021) - Mellor, Katie; Powell, Arfon G M T; James, Osian P; Robinson, David B; Hopkins, Luke; Egan, Richard John; Lewis, Wyn G
Abstract: Objectives: To compare proportional representation of healthcare specialty workers, in receipt of New Year Honours (NYHs) and examine system bias. Design: Observational study of UK honours system including comparative analysis of proportional representation of the UK medical workforce. Participants: Recipients of NYHs from 2010 to 2019. Main outcome measures: Absolute risk of receiving an NYH, related to medical specialty, gender and geographical region. Relative risk (RR) of receiving an NYH for services to healthcare related to specialty. Results: 11 207 NYHs were bestowed, with 368 (3.3%) awarded to healthcare professionals: 212 (57.6%) women, 156 (42.4%) men. The RR of a healthcare professional receiving an NYH was 0.76 (95% CI 0.68 to 0.84, p<0.001) when compared with the remaining UK workforce. Doctors received most NYHs (n=181), with public health, clinical oncology and general medicine specialties most likely to be rewarded (RR 20.35 (95% CI 9.61 to 43.08, p<0.001), 8.43 (95% CI 2.70 to 26.30, p<0.001) and 8.22 (95% CI 6.22 to 10.86, p<0.001)), respectively; anaesthetists received fewest NYHs (RR 0.52 (95% CI 0.13 to 2.10), p=0.305). Men were more likely to receive NYHs than women (OR 0.44, 95% CI 0.36 to 0.54; p<0.001). Two hundred and fifty-four NYHs (69.0%) were bestowed on residents of England (60, 16.3% London), 49 (13.3%) Scotland (p=0.003), 39 (10.6%) Wales (p<0.001) and 26 (7.1%) Northern-Ireland (p<0.001). Conclusions: Relative risk of receiving an NYH varied over 150-fold by specialty, twofold by gender and threefold by geographical location. Public health physicians are perceived to be the pick of the parade.